Life, work and capital in legal practice. Issue 1 (2nd January 2016) - Feenan, Dermot; Hand, James; Hough, Barry
Abstract: Career opportunities in legal practice remain significantly gendered, raced and classed in many countries. In particular, features of the organisation and culture of law firms in an era of neoliberalism exemplify how patterns of disadvantage for women and minority ethnic lawyers are sustained. This paper introduces a special issue of papers on the ongoing challenges faced by women and minorities, particularly in the large law firm, – an increasingly important sector of the legal profession. Both the special issue and this paper focus on three initiatives – diversity, work–life balance and wellbeing – purportedly designed to alleviate such disadvantage. The paper argues that distinctive features of capital in the large law firm, while ignoring the structural and underlying conditions for creation and maintenance of such disadvantage, limit the potential of such initiatives at the same time as renewing disadvantage.